PERMINTAAN TENAGA KERJA PADA SEKTOR INDUSTRI PENGOLAHAN BESAR DAN SEDANG DI SUMATERA - Esha Galang Gati Mahendra; Budiarty, Ida (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This study aims to analyze the demand for labor in large and medium industries in Sumatra. The determinants of labor demand in this study are the Regional Minimum Wage, Gross Regional Domestic Product and Total Labor Force. The minimum wage is one of the determining variables because the sample in this study are production workers. The data used is industrial survey panel data for 2010-2019 for 10 provinces on the island of Sumatra. The structural model that has been estimated for each industry and has been tested significantly is REM. The estimation results show that the provincial minimum wage, gross regional domestic product and the size of the workforce have a positive and significant effect on employment. In medium industries, the estimation results show that the minimum wage has a positive and insignificant effect, gross regional domestic product has a positive and significant effect, the size of the workforce has a negative effect but is not significant.